The Implementation of School Disaster Preparedness Policy (SSB) In SMPN 2 North Rao District Pasaman - Nursanti, Ida; Khairani, Khairani (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research describes 1) the implementation of Disaster Preparedness School (DPS) in SMPN 2 Rao Utara, and 2) supporting and inhibiting factors. This research was descriptive qualitative. The Subjects of this research were principals, teachers, and students. Data collection techniques used interview techniques, questionnaires, observation, and documentation. The result of this research shows that 1) the implementation DPS in SMPN 2 Rao Utara was done through three activities that were organizing, interpretation, and application. DPS organizing was a cooperation with various parties, making contingency plan of documents, and loading disaster mitigation material on the curriculum. The DPS interpretation was to draw up guidelines for the contingency plan of documents, the loading of disaster mitigation, and the vision of the school mission, and to provide supporting infrastructure. 2) DPS supporting factors in cooperation with the institution, have supporting tools, assistance from BPBD, while the factors inhibiting student turnover of new teachings, many school activities, less funding simulation activities, and less communication with the institution. Indicates that SMPN 2 Rao Utara, has been able to implement in terms of building structure, has been implemented DPS.